A review on the application of blind deconvolution in machinery fault diagnosis. (15th January 2022) - Miao, Yonghao; Zhang, Boyao; Lin, Jing; Zhao, Ming; Liu, Hanyang; Liu, Zongyang; Li, Hao
Highlights: A review of blind deconvolution methods (BDMs) in machinery fault diagnosis. History, principle, classic method and applications of BDMs are reviewed. Modified BDMs are classified to review according to their basic principle and merits and limitations are verified. Future prospects of BDMs in machinery fault detection is discussed. Abstract: Fault diagnosis is of significance for ensuring the safe and reliable operation of machinery equipment. Due to the heavy noise and interference, it is difficult to detect the fault directly from the measured signal. Hence, signal processing techniques that can achieve feature extraction, signal denoising, and fault identification are the most common tools in the field. Blind deconvolution methods (BDMs), as one of the most classic methods, have been studied extensively and applied fully for machinery fault diagnosis. Up to now, plenty of publications about the studies and applications of BDMs for machinery fault diagnosis have been presented to academic journals, technical reports, and conference proceedings. This paper intends to survey and summarize the current progress of BDMs applied in machinery fault diagnosis, as well as provides a comprehensive review of BDMs from history to state-of-the-art methods and finally to research prospects. Firstly, the theoretical background and brief history of BDMs are introduced. Secondly, the modified BDMs are classified to review their basic principles. After that their merits and limitations as well as the performance analysis are summarized. Thirdly, the research and application on machinery fault detection using BDMs are overviewed. Finally, the prospects of BDMs in machinery fault diagnosis are discussed.